Optimización de recursos humanos y calidad de la atención en el Centro de Salud B Santa Rosa - Juca Solís, Karen Betsabeth (My University, 2025)
This study analyzes the relationship between the optimization of human resources and the quality of care at the Centro de Salud B Santa Rosa, a primary care unit of the IESS in Ecuador. The research is based on the premise that effective human talent management directly impacts the quality of health services. Challenges such as excessive workload, limited ongoing training, and deficiencies in the organizational climate were identified, all of which negatively affect both staff performance and user perception. The study followed a quantitative, descriptive, and correlational approach. The population consisted of 31 staff members and 331 users, using expert-validated Likert-scale instruments. Statistical techniques such as multiple linear regression and Spearman’s rank correlation coefficient were applied to establish relationships between variables. The results reveal low satisfaction levels among staff in key areas such as planning, time management, and training. From the users’ perspective, critical views were evident in areas such as waiting time and service efficiency. Although no statistically significant correlations were found between the perceptions of staff and users, critical areas for intervention were identified, including workplace climate, internal organization, and professional development. It is concluded that improving human talent management through strategic planning, continuous training, and the reinforcement of a positive work environment is essential to enhance the quality of care in health units. This study provides empirical evidence useful for designing institutional strategies aimed at strengthening primary healthcare services.
El presente estudio analiza la relación entre la optimización de los recursos humanos y la calidad de la atención en el Centro de Salud B Santa Rosa, una unidad de primer nivel del IESS en Ecuador. La investigación parte de la premisa de que una adecuada gestión del talento humano impacta directamente en la calidad de los servicios de salud. Se identifican desafíos como la sobrecarga laboral, la escasa capacitación y las deficiencias en el clima organizacional, que afectan tanto el desempeño del personal como la percepción del usuario. El estudio se desarrolló bajo un enfoque cuantitativo, de tipo descriptivo y correlacional. La población incluyó a 31 trabajadores y 331 usuarios, utilizando instrumentos tipo Likert validados por expertos. Se aplicaron técnicas estadísticas como la regresión lineal múltiple y el coeficiente de correlación de Spearman para establecer relaciones entre variables. Los resultados revelan percepciones bajas de satisfacción del personal en dimensiones clave como planificación, uso del tiempo y capacitación. Desde la perspectiva de los usuarios, se evidenció una percepción crítica en dimensiones como tiempo de espera y eficiencia. Aunque no se hallaron correlaciones significativas entre percepciones del personal y las de los usuarios, se identificaron áreas críticas para intervención, como el clima laboral, la organización interna y el desarrollo profesional. Se concluye que la mejora en la gestión del talento humano, mediante planificación estratégica, formación continua y fortalecimiento del ambiente laboral, es esencial para elevar la calidad de atención en unidades de salud. Este estudio aporta evidencia empírica útil para diseñar estrategias institucionales orientadas al fortalecimiento del primer nivel de atención.
Keywords: ATENCIÓN PRIMARIA; CALIDAD DE ATENCIÓN; CARGA LABORAL; EFICIENCIA ORGANIZACIONAL